Analisis Pengaruh Pelayanan Perusahaan terhadap Loyalitas Pelanggan (Studi Pada Bengkel Resmi Yamaha Adhi Motor di Rembiga Mataram) - Miftah Ruli Hartanto; Sri Darwini; Lalu M. Furkan (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2020)
This study aims to determine how the level of customer satisfaction, as well as to determine whether the level of customer satisfaction has a significant effect on customer loyalty at the Yamaha Adhi Motor Official Workshop in Rembiga Mataram. This type of research is descriptive research and data collection techniques used are questionnaires, interviews, observation, and documentation. This research was conducted at the Yamaha Adhi Motor Workshop in Rembiga Mataram, the data collection technique used a sample survey technique and the determination of respondents using purposive sampling technique where as many as 50 people were made respondents. The data collection tool used in this study was a questionnaire, in which the variables were analyzed qualitatively using a Likert scale and quantitatively using chi square analysis. Based on the research that has been done, it shows that consumers at the Yamaha Adhi Motor Workshop in Rembiga Mataram are 35 people (70%) who are very satisfied with the elements of service provided, 10 respondents (20%) are satisfied, and the remaining 5 people (10 %) expressed dissatisfaction. The results of the calculation with the average score of the level of consumer loyalty, as many as 21 people (42%) have a level of loyalty at the Yamaha Adhi Motor Official Workshop are very loyal, 11 people (22%) say they are loyal, while the remaining 18 people (36%) stated loyal enough. Quantitatively, to test the proposed hypothesis and analyze the effect of the independent variable on the dependent variable, the calculation results obtained by the X2 value is 18.25 and this value is greater than the X2 table value of 9.49 at α = 0.05 and df = 4, which proves that customer satisfaction has significant influence on the level of consumer loyalty, because X2h> X2t. Furthermore, it is also known that the level of closeness of the relationship between variables is strong, as evidenced by the contingency coefficient (C) of 0.52, which is close to the Cmaximal value of 0.71, which in fact fulfills the requirement that the C value is greater than half the C max value.